Dichotomy: A Practical Architecture for Multi-channel IEEE 802.11 Multi-hop Networks - Tan, Kun; Wu, Haitao; Zhang, Yongguang; Zhang, Qian; Li, Li Erran (Microsoft, 2006)
In this paper, we present Dichotomy, a novel practical architecture that exploits channel diversity to improve wireless multi-hop network throughput with a single transceiver. Unlike previous link-layer multichannel work that requires complex coordination and is difficult to implement, Dichotomy operates without clock synchronization, and with greatly reduced switching overhead. The core idea is to strategically select a subset of nodes as anchors whose channels seldom change; while other nodes are hoppers that dynamically switch its radio among channels of neighboring anchors. Communications are enforced between anchor-hopper pairs or same-channel anchor-anchor pairs. It uses localized distributed algorithm to select anchors and assign channels to anchors, while maximizing the channel diversity and keeping the network well connected. We implement Dichotomy as a software shim layer between IP and MAC, and evaluate it in a real test-bed. Experimental results show that Dichotomy effectively boosts the network throughput up to 100%. We further conduct extensive simulations and demonstrate that the Dichotomy architecture is scalable and achieves better or comparable performance than other previous work.